Confidential registration in health services: randomised controlled trial. Issue 6 (19th May 2006) - Shepherd, J P; Ho, M; Shepherd, H R; Sivarajasingam, V
Abstract : Background: Human rights legislation safeguards the privacy and dignity of patients. Objective: To assess the effectiveness in terms of patient assessed privacy of confidential registration. Design: Randomised controlled trial. Setting: Emergency Department, University Hospital of Wales. Participants: A total of 302 patients aged over 15 years. Main outcome measures: Binary choices and ordinal visual analogue scores from a validated questionnaire on self reported measures: patient ability and preference to speak to receptionists and disclose confidential information without being overhead and concern about disclosure of items of confidential personal information. Results: Patients who registered in a screened area felt significantly more able to tell receptionists things they did not want others to hear. Control patients were significantly more concerned than intervention patients that others heard their name, address, date of birth, reason for emergency department attendance, and telephone number, but not their marital status. Overall, intervention patients were less concerned about disclosure of information and that they had been overheard. Conclusions: Patients value privacy when they register and are concerned if others can hear them tell receptionists who they are, how to contact them, and why they are there. Confidential registration should be instituted in health services. Confidential registration increased patient privacy and should be instituted in health services.